-sqrt(x)/(x + one hundred)^ two + one /(two *sqrt(x)*(x + one hundred)) = zero
minus square root of (x) divide by (x plus 100) squared plus 1 divide by (2 multiply by square root of (x) multiply by (x plus 100)) equally 0
minus square root of (x) divide by (x plus one hundred) to the power of two plus one divide by (two multiply by square root of (x) multiply by (x plus one hundred)) equally zero
-√(x)/(x + 100)^2 + 1/(2*√(x)*(x + 100)) = 0
-sqrt(x)/(x + 100)2 + 1/(2*sqrt(x)*(x + 100)) = 0
-sqrtx/x + 1002 + 1/2*sqrtx*x + 100 = 0
-sqrt(x)/(x + 100)² + 1/(2*sqrt(x)*(x + 100)) = 0
-sqrt(x)/(x + 100) to the power of 2 + 1/(2*sqrt(x)*(x + 100)) = 0
-sqrt(x)/(x + 100)^2 + 1/(2sqrt(x)(x + 100)) = 0
-sqrt(x)/(x + 100)2 + 1/(2sqrt(x)(x + 100)) = 0
-sqrtx/x + 1002 + 1/2sqrtxx + 100 = 0
-sqrtx/x + 100^2 + 1/2sqrtxx + 100 = 0
-sqrt(x) divide by (x + 100)^2 + 1 divide by (2*sqrt(x)*(x + 100)) = 0